Priority Reforms for the Government of Lebanon - World Bank (Washington, DC, 2017)
This Policy Paper presents a menu of reforms that would enable the country to rapidly and significantly turn the page of inaction and decline and return the country to a prosperous and inclusive development path. To that end, reforms are prioritized over two time horizons—the first 100 days of the new Government and the medium term. The immediate set of reforms suggested aim at establishing a record of achievements and government credibility that is currently sorely absent; without such a clear statement, policymaking effectiveness will be limited. They will also set the platform for the medium term. Failing to move swiftly on reforms would not only damage the credibility of this government, diminish its chances of success during the upcoming elections, but would also increase the already high level of skepticism that the Lebanese people and the international community harbor when it comes to Lebanon's capacity to take on serious and transformational changes. In short, and contrary to some wishes, the international community's engagement and commitment to help Lebanon will hinge heavily on Lebanon helping itself. The seeming end of a long political stalemate offers Lebanon a unique window of opportunity to mitigate impending risks and tackle longstanding and, by now, pressing development challenges. This sense of urgency is reinforced by a palpable deterioration in the quality of public services, institutions, governance and the business climate, to name a few. Macroeconomic risks and institutional lethargy, have also been compounded by the Syrian war, taking a toll on the economy, which, even prior to the regional turmoil, exhibited significant shortfalls in the provision of more and better jobs. Furthermore, the influx of displaced persons from Syria (estimated at over one million by UNHCR as of September 2016) has placed added strain on Lebanon’s education, health, municipal and other sectors, while exacerbating already notable subnational inequalities. This Policy Paper presents a menu of reforms that would enable the country to rapidly and significantly turn the page of inaction and decline and return the country to a prosperous and inclusive development path. To that end, reforms are prioritized over two time horizons—the first 100 days of the new Government and the medium term. The immediate set of reforms suggested aim at establishing a record of achievements and government credibility that is currently sorely absent; without such a clear statement, policymaking effectiveness will be limited. They will also set the platform for the medium term. Failing to move swiftly on reforms would not only damage the credibility of this government, diminish its chances of success during the upcoming elections, but would also increase the already high level of skepticism that the Lebanese people and the international community harbor when it comes to Lebanon's capacity to take on serious and transformational changes. In short, and contrary to some wishes, the international community's engagement and commitment to help Lebanon will hinge heavily on Lebanon helping itself.